Studi Komparasi Media Pembelajaran Visual Dan Audio Terhadap Hasil Belajar IPS Siswa Kelas III SD Muhammadiyah 1 Ketelan Tahun 2015/2016 - Ayunita, Norma (2016)
ABSTRACT Norma Ayunita / A510120021. COMPARISON STUDY OF LEARNING MEDIA VISUAL AND AUDIO TO IPS LEARNING OUTCOMES OF CLASS III SD MUHAMMADIYAH 1 KETEALAN YEAR 2015/2016. Essay. The Faculty of Education, University of Muhammadiyah Surakarta. January, 2016. The purpose of this study to determine: (1) the difference in the results of social studies using visual and audio media on a third-grade students of SD Muhammadiyah 1 Ketelan year 2015/2016. (2) better learning media used to learning outcomes IPS third grade students of SD Muhammadiyah 1 Ketelan year 2015/2016. This research is a quantitative research design eksperrimen. The research subject is class III C and D class III SD Muhammadiyah 1 Ketelan. Data collection techniques were used that test and documentation. Test instrument used in this study is to test the validity and reliability. Data analysis techniques using T test. as the terms of data analysis performed using test Liliefors normality test and homogeneity test using Bartlett test. Based on the analysis of data in the 0.05 α showed no difference in the results of social studies using visual and audio media pembeljaran with t_obs= 0,165 < t_tabel= 2,00172. The average results of social studies using visual media is 74 and the average value of the results of social studies using the audio media is 71. So better visual learning media use the results of social studies students of class III rather than using the audio media. Keywords : visual media , audio media , learning outcomes IPS